2014
DOI: 10.1007/s00066-014-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy after salvage lymph node dissection because of nodal relapse of prostate cancer versus salvage lymph node dissection only

Abstract: ART after salvage-LND provides stable local control in TR and results in overall significant improved next-relapse-free survival, compared to patients who received surgery only in case of nodal PCa-relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 33 publications
3
51
0
2
Order By: Relevance
“…Similar, Rischke et al found a significant improvement in 5-year next-relapse-free survival when adjuvant pelvic EBRT was added to salvage PLND (27). In contrast, we observed a local relapse in 7% of our pN1 PC patients compared to 3% in the pN0 population.…”
supporting
confidence: 87%
“…Similar, Rischke et al found a significant improvement in 5-year next-relapse-free survival when adjuvant pelvic EBRT was added to salvage PLND (27). In contrast, we observed a local relapse in 7% of our pN1 PC patients compared to 3% in the pN0 population.…”
supporting
confidence: 87%
“…In cases of isolated lymph node metastases, there is also the option to perform a salvage lymph node dissection of the pelvis with [27,28] or without [29] adjuvant radiotherapy. Complications of this surgical metastasis directed approach are bleeding, infection, ileus, hydronephrosis and drainage requiring lymphocele [30].…”
Section: Discussionmentioning
confidence: 99%
“…There is also the option to perform salvage lymph node dissection of the pelvis with (25,26) or without (27,28) adjuvant radiotherapy, taking into account that adjuvant irradiation results in delayed relapse within the treated region, but has no effect on the relapse pattern outside the treated region. Therefore, the combination of two local treatment modalities within the same anatomic region does not offer any additional benefit for patients with prostate cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of two local treatment modalities within the same anatomic region does not offer any additional benefit for patients with prostate cancer (27). In addition, surgery has the risk of common perioperative complications (25)(26)(27)(28). To our knowledge, no prospective studies comparing salvage lymph node dissection with or without radiotherapy using PSMA-PET/CT for staging purposes have been conducted.…”
Section: Discussionmentioning
confidence: 99%